Effect of salinity on embryonic development eggs hatching rate and of larvael survival of Common Carb - Jabber, A. A.; Mohamed, A. R. M.; Salh, K. I. (Iraqi Journal of Aquaculture, 2022)
This study focus upon the beneficial capability of brackish water embryonic development hatching fish eggs embryo genes of common carp, Cyprinus carpio ( L.). different concentrations were used. (2-16‰). The aeration hatching technique was used in the hatching of eggs, and the hatched larvae were incubated in the same salt concentrations. The nursing was done in plastic containers for eight weeks in the same salt concentrationsThe results showed that the higher ratio of development of the embryos which was 94% at salt concentration of 6‰ after the first six hours of the eggs incubation, and decreased to85.5% in the concentration of 6‰ after 48 hours of incubation. The period of hatching of eggs ranged between 52-72 hours in the concentrations 2-12‰ . The high survival ratio for larvae was 95 % at the salinity of 2 ‰, while the embryo died directly after hatching at the salinity 12‰.The duration of yolk sac absorption for common carp larvae were ranged between 2-3 days at the salinity of 2‰ and 5-7 days at the salinity of 8‰.The gas bladder of the common carp appeared within 3-4 days at the 2 and 4‰ .average weight 1.9 g in the salinity of 4‰ and the lowest weight was 0.72g of salinity of 8‰The highest average daily weight gain increased for common carp and it was 0.0344 g at salinity of 4‰.